Taṭbīq aṭ-Ṭarīqah al-Mu`addalah Fī Ta`līm Qawā`id al-Hamzah Li Tarqiyah Saiṭarah aṭ-Ṭālibāt `Alā Fahm Kitābah al-Hamzah (Dirāsah Tajrībiyah Li al-Marḥalah al-Mutawassiṭah Bi Ma`had Inṣāf al-Dīn) - Yulia Safitri; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The research problem in this thesis is that many students of class two mistakenly write hamzah, for example in the verb "اطمأن", in the form of fiil madhi written on alif, and in the form of fi mudhari 'written on “ya”, such as: يطمئن. Most of them make mistakes in writing it because they are ineffective and are not focused in learning the rules of writing hamzah and they cannot distinguish between hamzah in Arabic writing because the lessons of imla 'and insha' are important tools for written expression in terms of truth and integrity the mistak. The purpose of this thesis is to find out the teacher and student activities in the application of the modified method in the learning of the method of hamzah for Second grade level students of Junior High School Inshafuddin Boarding School and to identify students' responses in the application of the modified method of learning the method of Hamzah and to identify the effectiveness of the application of the modified method in the learning of the Hamzah Method for Junior High School of Integrated Inshafuddin Boarding School. The method used by researchers to compile this thesis is an experimental approach, which is a scientific research method in which researchers use to determine the effect of causes (independent variables) on outcomes (dependent variables), which have a clear effect on the progress of natural science. The results obtained from this study are the application of a modified method in teaching the method of hamzah to run well fully which learning the method of hamzah in an interesting and easy way for students and can increase their desire to learn it. Likewise the students' response to applying the modified method in teaching the method of hamzah is good because students can answer all questions easily and improve their ability to write hamzah. In addition, the application of the modified method is also effective as stated in post test after the learning process of the Hamza Method. The researcher obtained different pre-test and post-test results in which the null hypothesis was rejected and the alternative hypothesis was accepted with the result ("T" Test) higher than the results of "T" Table in the form of 2.81 <5.36 <07, 2 according to the level of significance. Therefore, the modified method of teaching the method of hamzah is very effective and can improve the ability of students to write hamzah.